2010
DOI: 10.1370/afm.1181
|View full text |Cite
|
Sign up to set email alerts
|

Residency "Dashboard": Family Medicine GME's Step Towards Transparency and Accountability?

Abstract: could consistently occur simultaneously with efforts to support the core content requirements of the family medicine clerkship, exportable teaching models for use in dispersed clinical settings may emerge. The differences in the number of FTE's devoted to support medical student education varied greatly in the ADFM Quick Hitter Survey with the differences appearing not attributable to class size. The survey reveals responses concerning a variety of tracts for medical student learning to include rural, urban, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Determining KPIs and benchmark standards: Selecting the type of indicators which should be included in dashboards is important. Depending on its situation, each department needs to measure the indicators related to its own area of performance, not all the indicators ( 9 , 26 ), in other words, indicators which are critical and special to the quality of their performance ( 27 ). Each indicator is selected according to business purpose and the ability to be gathered easily through standard business functions ( 28 ) and besides accurate measurement of the indicator ( 9 ), we should identify dashboards metrics from regulatory standards which we need for accreditation or credentials ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Determining KPIs and benchmark standards: Selecting the type of indicators which should be included in dashboards is important. Depending on its situation, each department needs to measure the indicators related to its own area of performance, not all the indicators ( 9 , 26 ), in other words, indicators which are critical and special to the quality of their performance ( 27 ). Each indicator is selected according to business purpose and the ability to be gathered easily through standard business functions ( 28 ) and besides accurate measurement of the indicator ( 9 ), we should identify dashboards metrics from regulatory standards which we need for accreditation or credentials ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…By giving programs aspirational targets for metrics around several accreditation domains, the RPI sought to spur the greater family medicine residency community to strive to exceed minimum standards. 11,12 Our analysis of the 82 programs with 3 or more years of RPI data revealed that the tool did not result in significant changes for most metrics. Although approximately 40% of the 82 programs with longitudinal data available for analysis consistently achieved aspirational (green) targets for most of the metrics, there were not significant improvements in the percentage of programs achieving those targets over time.…”
Section: Discussionmentioning
confidence: 93%
“…The AFMRD Board of Directors proposed the development of a dashboard-style tool, called the residency performance index (RPI), to help programs in the process of selfimprovement. 11,12 We have previously described the process to develop this tool and its initial successes and challenges. 13,14 In 2018, the AFMRD Board made the decision to sunset the RPI due to insufficient return on investment as demonstrated by increasing software costs and staff time coupled with lack of growth in participation and only modest improvement in quality.…”
Section: Original Articlesmentioning
confidence: 99%
“…Selecting the type of indicators which should be included in dashboard is important. Depending on its situation, each department needs to measure the indicators related to its own area of performance, not all the indicators [41,48], but indicators which are critical and special to the quality of their performance [49]. Each indicator is selected according to the business purpose and the ability to be gathered easily through standard business functions [50].…”
Section: Discussionmentioning
confidence: 99%